After Gunshot: A Qualitative Evidence Synthesis on Community Recovery from Mass Violence - Bleoaja Cayla (European Review Of Applied Sociology)
Incidents of mass violence, defined as occurring in a public place with at least four fatalities and not related to domestic violence or other criminal activity, have left scars on the social psyche of communities that have survived and witnessed them. While their psychological ramifications are increasingly considered, little research has addressed social behavior in the aftermath on a community-level. This Qualitative Evidence Synthesis (QES) aims to address an identified gap in research with an examination of the mechanisms of communal resilience and healing after an incident of mass violence. The search strategy yielded 7,106 records, of which 5,897 were screened by title and abstract and 116 by full text. Communities largely engaged in three interconnected processes. First, they moved towards convergence through social support, shared identity, and public expression of grief. Secondly, they engaged in meaning-making through spirituality, positive reframing, and collective narratives. Lastly, they participated in acts of transfiguration through altruism, mobilization, and reconstruction. Implications for policy include moving beyond a medical model and utilizing internal community assets, strengthening collaborative networks that promote social cohesion, and investing in existing community assets and resources.